DETERMINANTS OF FAIR VALUE FINANCIAL INSTRUMENT AND SHARE-BASED PAYMENT DISCLOSURE PATTERNS OF AUSTRALIAN LISTED FIRMS - Wei, Meng; Taylor, Grantley (The journal of contemporary issues in business and government, 2009)
This paper investigates the extent of mandatory Fair Value Financial Instrument Disclosures and Fair Value Share-Based Payment Disclosures in the first full year annual report prepared in accordance with the International Financial Reporting Standards of the top 100 Australian listed companies. The results demonstrate that internationalisation is a factor which is significantly and positively associated with fair value share-based payment disclosure patterns and the strength of corporate governance structure and leverage are positively and significantly associated with fair value financial instrument disclosure patterns. This paper contributes to an understanding of the extent and rationale behind Australian listed firms’ fair value disclosure practices.